RANCANG BANGUN APLIKASI E-PRAKERIN PADA SMKN 3 LUWU BERBASIS WEB - Ulvah, Ulvah; Rosmiati, Rosmiati; Sukmawati, Sukmawati (Jurnal INSYPRO (Information System and Processing), 2024)
Information technology that is developing so rapidly requires all fields in human life to utilize technology to help people’s daily activities. Likewise, the education sector must follow the momentum of the development of the era of increasingly advanced technology use which will provide convenience for all parties. SMKN 3 Luwu is a vocational high school that collaborates with industry through an industrial work practice program or commonly called prakerin during education. SMKN 3 Luwu needs an application that supports the management of pre-kindergarten. The Prakerin registration process for SMKN 3 Luwu is still carried out by students going to the Prakerin organizing committee to propose a location or place where they want to do Prakerin later, this is considered inefficient by looking at the current use of technology that can be used to efficiently register for students who want to do Prakerin. Currently, the use of information technology (computers and the internet) has been adjusted to its needs in improving the performance of admins in certain schools. The information system development methodology used is the Waterfall model. The information system is designed and built based on a website using the PHP programming languages MyAdmin and MySQL as its database. By designing and building this application, it will make it easier for students and the committee in the pre-registration process.